Fatores associados à ingestão de frutas e verduras de adolescentes : uma abordagem ecológica - Raizel, Raquel (2013)
Introduction: to promote healthy eating is necessary to identify the factors that affect eating behavior. Objective: synthesize the available evidence on the factors associated with fruit and vegetable consumption among adolescents. Methods: we conducted a systematic review of studies indexed in databases LILACS, SciELO, ADOLEC and PubMed, using the terms: fruits and vegetables. The search was finished in December 2012. We included original articles with adolescents 10 to 19 years, who investigated the consumption of fruit and vegetables as outcome, published in Portuguese, Spanish or English. Results: The review included 39 studies and the key issues investigated were related with: socioeconomic, demographic, family and individual factors. Family income, parent’s education and healthy eating, support and positive relationships with colleagues are positively associated with intake of fruits and vegetables of adolescents. However, risk behaviors such as drinking, smoking, sedentary activities or be physically inactive show inverse associations. Food insecurity, unhealthy food availability, access to information on radio and TV commercial, plus housing in urban areas are less studied factors, but negatively affect the food consumption. Moreover, the emotional attachment with parents and dietary rules also represent important determinants. Conclusions: Socioeconomic, demographic and lifestyle-related factors, the influence of family and friends represent significant determinants of intake of fruits and vegetables in adolescence.